Cesarean section rates and local resources for perinatal care in Japan: A nationwide ecological study using the national database of health insurance claims. Issue 2 (2nd November 2017) - Maeda, Eri; Ishihara, Osamu; Tomio, Jun; Sato, Aya; Terada, Yukihiro; Kobayashi, Yasuki; Murata, Katsuyuki
Abstract: Aim: High cesarean section (CS) rates in middle and high‐income countries are partly attributable to provider factors, such as staffing patterns and fear of litigation. However, the relationship between CS rates and healthcare resources in the community is poorly understood. Official data on CS rates has been particularly limited in Japan. In this study, we examined nationwide CS statistics and evaluated the association with local resources for perinatal care. Methods: We used accumulated data for CS registered in the Japan National Database of health insurance claims in 2013 and calculated crude and age‐standardized CS rates at national and prefectural levels. We analyzed the ecological associations with supply of obstetricians and institution and scale of obstetric facilities using multiple regression models. Results: There were 190 361 cesarean deliveries in 2013, giving an overall CS rate of 18.5% (elective CS rates 11.0%), which varied by prefecture from 14.0% to 25.6%. In multiple regression analyses, the areal number of obstetricians (standardized regression coefficient [β] = −0.58), the proportion of births at small‐scale institutions (β = 0.36) and the number of beds at neonatal intensive care units per birth (β = −0.20) were significantly associated with the age‐standardized elective CS rate after adjusting for socioeconomic factors ( R 2 for the model = 0.40). Conclusions: Higher elective CS rates might be associated with limited or unconsolidated medical resources. Policymakers should be aware of regional differences and the possible effects of perinatal care resources on CS rates.